Hidrolisis Mikroalga Tetraselmis chuii Dengan Variasi Konsentrasi Asam Sulfat Dan Temperatur - Gilda Miranda; Amun Amri; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Glucose is a monosaccharide which can be used as an energy source in bio-battery, to produce intermediate products (hydroxymethylfurfural, furfural, levulinic acid, and formic acid), and can be converted into bioethanol. Glucose is a sugar monomer produced after hydrolysis of cellulose and hemicellulose chains in land plants and water plants. Microalgae is a water plant that has a big potential to be converted into glucose. It has been known to use light and various carbon sources to produce carbohydrate. Tetraselmis chuii is a green microalgae, containing a large number of carbohydrate, fat, protein, vitamin, and mineral. As a green microalgae, Tetraselmis chuii has a cellulose and hemicellulose components in its cell wall without a lignin content. This research focused on the hydrolysis of microalgae using variation of sulphuric acid concentration and temperature as variables to produce glucose. Microalgae feedstock was mixed with different concentrations of sulphuric acid between 0.25-1.75% (v/v). Hydrolysis process was conducted under low temperatures at 60 and 70 oC for 30 minutes. The glucose was analyzed quantitatively using Spectrophotometer UV-Vis. The results showed that the highest glucose yield obtained was 48,40% and this was achieved when the hydrolysis occurred at 70 oC with 1.75% (v/v) sulphuric acid addition. This study revealed that the temperature and the sulphuric acid concentration are the important factors during acid hydrolysis of microalgae for glucose production.  Keywords : glucose, dilute sulphuric acid, hydrolysis, temperature, Tetraselmis chuii.